Cervicovaginal secretions contribute to innate resistance to herpes simplex virus infection - John, Minnie (2005)
Defining and preserving the innate antiviral activity found in cervicovaginal secretions is critical. Cervicovaginal lavage (CVL) samples were obtained from 20 healthy women and evaluated for anti-herpes simplex virus (HSV) activity. CVL samples reduced HSV-2 yields by 23-fold (median), and the anti-HSV activity of CVL samples correlated with the concentration of human neutrophil peptides (HNP)-1-3. Both CVL samples and HNP-1-3 interacted with virus and prevented entry after binding. Substantially less protective activity was observed in CVL samples obtained from 20 human immunodeficiency virus-infected subjects, but the addition of CVL samples from healthy subjects enhanced the antiviral activity. The significance of the innate activity was further demonstrated by showing that CVL samples prevented murine genital herpes. Fourteen of 15 mice were protected from genital herpes if they were challenged with HSV-2 pretreated with CVL samples from healthy subjects. In contrast, all 15 mice challenged with untreated HSV-2 died. These findings are evidence that cervicovaginal secretions contribute to innate resistance to HSV-2 and identify defensins as contributors to this activity.